The Unfinished Educational Project of Tzvetan Stoyanov and his “Chinese Chronicle” - Nikolov, Toni (Acta Nova Humanistica: A Journal of Humanities Published by New Bulgarian University, 2025)
The article explores the unfinished educational and modernization project by the writer and thinker Tzvetan Stoyanov (1930–1971), who in the most difficult decades of communist Bulgaria managed to create his own large corpus of translations and texts, written in a relatively short period. A project that brought to the fore the concept of “Weltliteratur”, which he borrowed from Goethe to contrast it with the isolationism of “vale thinking”, as well as his fundamental research on the topic of alienation in contemporary culture. The article also attempts to reinterpret the essay “Chinese Chronicle” (1963) – an emblematic example of his “second” or philosophical prose, containing entire cycles of themes: “Dionysus”, “Orpheus”, “Karavelov and Botev”, “Lao Tzu and Confucius”, all the way to the “hippie subculture” and, of course, Dostoevsky – with “Genius and His Mentor”, which was intended to grow into a book about “death and resurrection”.